2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8036791
|View full text |Cite
|
Sign up to set email alerts
|

Smart mat system with pressure sensor array for unobtrusive sleep monitoring

Abstract: To improve the unobtrusiveness and comfortableness of sleep monitoring, we proposed the design and implementation of a smart mat which utilized flexible pressure sensor array and printed electrodes to monitor physiological and behavioral data during sleep. With the proposed novel soft seven-layer structure, the smart mat system can measure pressure distribution images and calculate respiratory rate of subjects. The function of this system was realized with pressure acquisition circuit controlled by Arduino pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…It is worth noting that with different conditions the subject lay on the mat, the peaks or valleys represented the end of inhalation correspondingly. As it is demonstrated in our previous study [ 19 ], when the subject lay on the mat with a supine posture and the back or waist part of body is in the measured area, the valleys in the respiratory waveform represented the end of inhalation. On the contrary, when the subject lay with a prone posture and the chest or abdomen part of body is in the measured area, the peaks represented the end of inhalation.…”
Section: Experiments and Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…It is worth noting that with different conditions the subject lay on the mat, the peaks or valleys represented the end of inhalation correspondingly. As it is demonstrated in our previous study [ 19 ], when the subject lay on the mat with a supine posture and the back or waist part of body is in the measured area, the valleys in the respiratory waveform represented the end of inhalation. On the contrary, when the subject lay with a prone posture and the chest or abdomen part of body is in the measured area, the peaks represented the end of inhalation.…”
Section: Experiments and Resultsmentioning
confidence: 72%
“…The experimental results demonstrated that this system would consume about 0.2 s to gather all 1024 pressure values, in other words, it need about 0.2 s to generate one frame. The time consumption was much faster than our previous work mentioned in [ 19 ] due to the modified signal acquisition program, but the program was not mentioned in this paper because it’s not the emphasis of this study.…”
Section: Experiments and Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Most studies show that the results of measurements using an accelerometer correspond to the values obtained from measurements by indirect and direct calorimetry, from monitoring physical activity. Sleep quality can be also evaluated by the movement during sleep time using the chip called the MPU-6050 [11].…”
Section: Introductionmentioning
confidence: 99%